UNIVERSALISME ISLAM DAN KOSMOPOLITISME PERADABAN - Dewi, Rosmala (Universitas Islam Negeri Raden Fatah Palembang, 2013)
Abstrak: Islam is a universal religion, the religion that itsenforcement is not limited by space and time. He is fit for theentire human race. Universality of Islam first of all looks at theconcept of monotheism into joint doctrine. Islam does notdistinguish skin, language, race, rank, degree.ملخص:الإسلام ھو دین عالمي، دین أن تنفیذه لا یقتصر بواسطة الفضاء والوقت .انھیصلح لجمیع الجنس البشري .عالمیة الإسلام أولا وقبل كل نظرة في مفھوم التوحیدفي العقیدة المشتركة .الإسلام لا یمیز اللون أو اللغة أو العرق أو رتبة، درجة.Kata Kunci: univeralisme, kosmopolitisme